2005
DOI: 10.2190/h0ar-68hr-rrpe-lrbh
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Differences in the Strategies Used by Middle Aged Adults to Solve a Block Design Task

Abstract: In the present study, it was proposed to investigate the effects of aging on the strategies used to solve a block design task and to establish whether these strategies may be associated with differential patterns of ability. Two groups of subjects, 30 young adults (aged 20-35 years) and 30 middle-aged adults (aged 45-60 years) were set a computer version of the Kohs task and a battery of tests. An age-related decrease in fluid intelligence (Gf) and visual-spatial ability (Gv) was observed, along with the fact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…One of the rare examples of developmental studies regarding strategy use in intelligence tests (Rozencwajg & Corroyer, 2001; Rozencwajg et al, 2005) was interested in Kohs’ block design task, a classic component of the Wechsler scales requiring subjects to reproduce an abstract design using colored cubes. The authors found three strategies in the block design task: a global strategy of assembling the blocks by trial-and-error, an analytic strategy of reproducing the design in rows or in columns, and a synthetic strategy of reproducing gestalts composed of multiple blocks.…”
Section: Strategy Use In Matrix Reasoning Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the rare examples of developmental studies regarding strategy use in intelligence tests (Rozencwajg & Corroyer, 2001; Rozencwajg et al, 2005) was interested in Kohs’ block design task, a classic component of the Wechsler scales requiring subjects to reproduce an abstract design using colored cubes. The authors found three strategies in the block design task: a global strategy of assembling the blocks by trial-and-error, an analytic strategy of reproducing the design in rows or in columns, and a synthetic strategy of reproducing gestalts composed of multiple blocks.…”
Section: Strategy Use In Matrix Reasoning Tasksmentioning
confidence: 99%
“…Fluid reasoning performance substantially increases during childhood, but it also decreases in older age: in the illustrative data set of J. Raven (2000, Figure 5), median SPM performance decreased from 44 out of 60 correct answers at 20 years old to just 24 out of 60 correct answers at 65 years old. It seems likely that these later changes are associated with a corresponding decline in constructive matching use, as is the case for Kohs' block design task (Rozencwajg et al, 2005). Studying strategy use in older adults would help elucidate the rest of the lifespan trajectory for qualitative underpinnings of behavior in the test most frequently used to measure intelligence.…”
Section: Other Directions For Future Studiesmentioning
confidence: 99%
“…Most of them have focused on major cognitive functions such as memory, reasoning, problem solving, and language, among others. The skills that present declines during the aging process are especially those that require an efficient working memory [5] [6] and fast processing [7], which means that the cognitive activities that rely more heavily on fluid intelligence, such as cognition and spatial reasoning, dealing with the maintenance and manipulation of visual images tend to be negatively affected by aging [8]. Studies have reported that early spatial deficits appear around 40 years of age and may become more pronounced after 50 years of age [9].…”
Section: Older Adults and The Webmentioning
confidence: 99%
“…By identifying the processes that underlie a subject's performance on intelligence tests, the researcher can gain insight into the subject's cognitive functioning by way of information that is not necessarily reflected in total scores on an intelligence test (Grégoire, 2004;Huteau & Lautrey, 1999;Rozencwajg, 2005;Rozencwajg, 2007;Rozencwajg & Bertoux, 2008;Rozencwajg & Corroyer, 2002;Rozencwajg, Lemoine, Rolland-Grot, & Bompard, 2005;Rozencwajg, Cherfi, Ferrandez, Lautrey, Lemoine, & Loarer, 2005). We focused in particular on the Arithmetic Subtest of the Wechsler Adult Intelligence Scale or WAIS-III (Wechsler, 2000), which remains the most widely used intelligence battery in the world (Castro, Meljac, & Joubert, 1996;Flanagan & Harrison, 2005).…”
Section: Frameworkmentioning
confidence: 99%